Simvastatin–ezetimibe combination therapy is associated with a lower rate of major adverse cardiac events in type 2 diabetics than high potency statins alone: A population-based dynamic cohort study. (1st July 2015) - Chang, Shang-Hung; Wu, Lung-Sheng; Lee, Cheng-Hung; Kuo, Chi-Tai; Liu, Jia-Rou; Wen, Ming-Shien; Chen, Wei-Jan; See, Lai-Chu; Yeh, Yung-Hsin
Abstract: Background: Recent trials have shown a reduction in the risk of major adverse cardiac events (MACE) with simvastatin–ezetimibe therapy in patients with acute coronary syndrome. The potential benefits of simvastatin–ezetimibe for patients at a lower risk of MACE are unclear. This study aimed to investigate the differences of MACE risk between patients with type 2 diabetes mellitus (DM) using simvastatin–ezetimibe or high potency statins. Methods: This population-based dynamic cohort study used data from the Taiwan National Health Insurance Database. The study subjects were patients with type 2 DM, aged between 40 and 75 years. The simvastatin–ezetimibe group took simvastatin–ezetimibe only, and the statin group took atorvastatin or rosuvastatin but not simvastatin or ezetimibe. The two groups were matched for age, gender, medication date, DM diagnosis date, hypertension, and cardiovascular complications. The outcome variable was new-onset MACE. Univariate and multivariate survival analyses were performed. Results: A total of 20, 485 patients (53% male; 4099 in the simvastatin–ezetimibe group and 16, 396 in the statin group) were included, with a mean age of 59.1 years. In a total of 37, 388 person-years, 1100 patients developed new-onset MACE. The annual incidence rate of new-onset MACE was lower in the simvastatin–ezetimibe group (2.61%) than that in the statin group (3.02%) (p = 0.0476). After Cox regression analysis, simvastatin–ezetimibe use was independently associated with a lower risk of MACE (HR, 0.77; 95% confidence interval 0.66–0.90). Conclusions: Compared to high potency statins alone, simvastatin–ezetimibe therapy was associated with a lower incidence of MACE in patients with type 2 DM.